Increases in Theta Oscillatory Activity During Episodic Memory Retrieval Following Mindfulness Meditation Training - Nyhus, Erika; Engel, William Andrew; Pitfield, Tomas Donatelli; Vakkur, Isabella Marie Wang (Frontiers in Human Neuroscience, 2019)
Mindfulness meditation has been shown to improve episodic memory and increase theta oscillations which are known to play a role in episodic memory retrieval. The present study examined the effect of mindfulness meditation on episodic memory retrieval and theta oscillations. Using a longitudinal design, subjects in the mindfulness meditation experimental group who underwent four weeks of mindfulness meditation training and practice were compared to a waitlist control group. During the pre-training and post-training experimental sessions subjects completed the Five Facet Mindfulness Questionnaire (FFMQ) and studied adjectives and either imagined a scene (Place Task) or judged its pleasantness (Pleasant Task). During the recognition test subjects decided which task was performed with each word ("Old Place Task" or "Old Pleasant Task") or "New". FFMQ scores and source discrimination were greater post-training than pre-training in the mindfulness meditation experimental group. EEG results revealed that for the mindfulness meditation experimental group theta power was greater post-training than pre-training in right frontal and left parietal channels and changes in FFMQ scores correlated with changes in theta oscillations in right frontal channels (n=20). The present results suggest that mindfulness meditation increases source memory retrieval and theta oscillations in a fronto-parietal network.